UPAYA MENINGKATKAN RASA INGIN TAHU DAN PRESTASI BELAJAR BAHASA JAWA MATERI MENULIS AKSARA JAWA MELALUI METODE STRUKTURAL ANALITIK SINTETIK - Widiasih, Hening Setio (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
The research is supported by the low curiosity and learning achievement of the students for the fifth graders SDN 2 Kaligondang. It aims: to improve the curiosity and learning achievement of Javanese Language on the topic of writing Javanese letters through synthetic analytic structural (SAS). The subject covered the fifth graders of SDN 2 Kaligondang consisted of 23 students. This classroom action research consisted of 2 cycles and each cycle had 2 meetings (per meeting included 2 teaching hours). The procedures included planning, acting, observing and reflecting. The data were collected by observation sheets of the teacher and students. The curiosity and learning achievement were gathered from test and questionnaire by the end of the cycle. The first cycle showed the mean of students’ curiosity 28.51%. The learning achievement in the first cycle was 60.86% with the mean 68.65. The second cycle showed that the mean of students’ curiosity was 34.13. The learning achievement was 86.95% with the mean 80.47. Thus, it could be drawn that Synthetic Analytic Structural could improve students’ curiosity and learning achievement for the fifth graders SDN 2 Kaligondang